AN UNUSUAL CASE OF DISSEMINATED TUBERCULOSIS FOLLOWING ANTIPSYCHOTIC THERAPY: AN AUTOPSY-BASED CASE REPORT (Journal of Forensic Medicine & Toxicology, 2022)
Tuberculosis (TB) is a communicable bacterial infection caused by Mycobacterium tuberculosis. It is the second leading fatal infectious disease after COVID-19. Tuberculosis also stands at 13th position, with respect to the leading cause of death. In 2020, around 86% of new tuberculosis cases were reported in 30 countries, of which two-thirds of cases were recorded in eight countries alone,with India leading the chart. Tuberculosis in a mentally ill patient is a common entity because of its common comorbidities, but prolonged antipsychotic drug therapy is rare. Here we discuss a case of a 36 years old female who was brought dead to casualty. She was apparently alright 10 days back and then developed symptoms like fever, breathlessness, and cough. She had severe anorexia and cachexia for the past few months. She has been under antipsychotic medication for schizophrenia. On autopsy, there were multiple whitish nodules present all over the intestine and various abdominal organs. We identified disseminated tuberculosis, and we analyzed histopathology and microbiology of tissues. We reported Ziehl-Neelsen staining negative for TB. Culture reported positive for Mycobacterium tuberculosis. Histopathology study tissues showed caseous necrotizing granulomas. As seen in some literature, tuberculosis can be seen in mentally ill patients, whereas literature showing the association between tuberculosis and antipsychotic drugs is less. This article highlights the association between such occurrence of tuberculosis while undertaking antipsychotic drug therapy.
Keywords: Tuberculosis; Nodule; Schizophrenia; Antipsychotic; Mental illness